2001
DOI: 10.1071/ea00017
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of retail beef yield from real time ultrasound measurements on live animals at three stages through growout and finishing

Abstract: Abstract. Analyses were performed to test the relationship between retail beef yield percentage (RBY) and real time ultrasound measurements taken at weaning, entry to finishing and preslaughter for animals finished under pasture and feedlot conditions to meet domestic, Korean and Japanese market specifications.The first analysis tested the power of live animal measurements (scanned P8 fat depth, scanned eye muscle area and liveweight) to predict RBY and contrasted this with a model containing these live animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
1
Order By: Relevance
“…Slightly higher correlations (0.17 to 0.33) between LMA (measured by ultrasound or directly on the carcass) and percentage of retail beef were reported in the studies of Greiner et al (2003) and Tait et al (2005). Wolcott et al (2001) found significant differences in the relationship between live animal measurements (live weight, ULMA, and USRPFAT) and retail beef percentage when estimated within market beef category, finishing regimen, and breed, a potential difference in the results between studies.…”
Section: Simple Correlationsmentioning
confidence: 81%
“…Slightly higher correlations (0.17 to 0.33) between LMA (measured by ultrasound or directly on the carcass) and percentage of retail beef were reported in the studies of Greiner et al (2003) and Tait et al (2005). Wolcott et al (2001) found significant differences in the relationship between live animal measurements (live weight, ULMA, and USRPFAT) and retail beef percentage when estimated within market beef category, finishing regimen, and breed, a potential difference in the results between studies.…”
Section: Simple Correlationsmentioning
confidence: 81%
“…This is in agreement with Bailey et al (1986) who obtained correlations of −0.16, 0.57 and 0.48 between scanned muscle area and carcass conformation score in light, medium and heavy weight categories, respectively, of Holstein bulls. Similarly, Wolcott et al (2001) found that the power of live animal measurements to predict retail meat yield percentage decreased as the time between scanning and slaughter increased.…”
Section: Ultrasound Muscle and Fat Depthmentioning
confidence: 94%
“…The USRIB and USEMA (M. longissimus thoracis et lumborum) measurements were taken at the 12th and 13th ribs (Barwick et al, 2009), the USP8 measurement was taken at the intersection between a line parallel to the spine from the tuber ischium and a line perpendicular to it from the spinous process of the third sacral vertebra (Johnston et al, 2003;Wolcott et al, 2009). All ultrasound measurements were taken by an accredited technician (Upton et al, 1999) with an Aloka 500V realtime ultrasound scanner using a 17-cm transducer (Corometrics Medical Systems Inc., Wallingford, CT), with vegetable oil as the coupling agent, and the fat depths were recorded using callipers built into the scanner (Wolcott et al, 2001).…”
Section: Data For Model Developmentmentioning
confidence: 99%